L’E.S.W.T.: Extracorporeal Shock Wave Therapy - Cervera, G.P.; Tammaro, N.; Romano, L.; Toro, G.; Pellegrino, A. (Lo Scalpello - Journal, 2019)
L’E.S.W.T.: EXTRACORPOREAL SHOCK WAVE THERAPYExtracorporeal Shock Wave Therapy (ESWT) is an effective and safe non-invasive therapeutic option for variousmusculoskeletal pathologies. Extracorporeal shockwave therapy has been widely used in many musculoskeletalproblems over the last 25–30 years, for example in case of pseudoarthrosis, plantar fasciitis, lateral epicondylitis,shoulder calcific tendinitis, Achilles tendinopathy, and osteonecrosis of the femoral head. Though the exact effects havenot been proven, it has been suggested that shock waves accelerate tissue healing, reduce calcification, and inhibit painreceptors with denervation. As an economic and noninvasive physical therapy with good clinical effects, applicationsof ESWT have gradually increased in recent years.